O33-6 Understanding risky health behaviours in illinois workers: findings from the 2013 behavioural risk factor surveillance system (brfss) using the industry and occupation module. (1st September 2016) - Madrigal, Jessica; Persky, Victoria; Forst, Linda
Abstract : In 2013, Illinois employed over 5 million people in various industries and occupations throughout the state. It is well known that working conditions can negatively impact health. However, state health data systems often lack information regarding occupation and industry, thus limiting opportunities to develop targeted health interventions in workplaces. Recently, the National Institute for Occupational Safety and Health (NIOSH) added industry and occupation questions to the 2013 Illinois Behavioural Risk Factor Surveillance System (BRFSS) survey. Overall, 2, 962 respondents (53%) sampled reported having been employed within the last year. Occupation and industry codes based on the U.S. Census Occupation and Industry Classification System were assigned for 2, 467 (83%) and 2, 533 (86%) of employed respondents, respectively. Coded responses were categorised into 23 occupation and 21 industry groups and compared to 2013 state employment estimates from the Bureau of Labour Statistics. Estimated BRFSS distributions were similar to the Illinois workforce. Weighted SAS survey procedures were used to assess prevalence of smoking, seatbelt use, binge drinking, adequate sleep, and immunisation for each industry and occupation group. Prevalence of smoking, flu shots, and binge drinking varied by industry (p-values=0.0001–0.006) and occupation (p-values=0.0001–0.008). After adjusting for confounders (e.g., age, sex, education, race) using logistic regression, increased prevalence of binge drinking was observed among computer workers (prevalence ratio (PR) = 2.8, 95% CI: 1.1–6.9) and increased prevalence of non-adherence to flu immunisation was observed among construction workers (PR = 3.8, 95% CI: 1.4–10.2). Significant adherence to flu immunisation recommendations was observed among healthcare, education and transportation workers (PR = 0.25–0.56, p = 0.0001–0.0453). Compared to the public administration industry, increased prevalence of binge drinking in the healthcare industry was observed (PR = 2.6, 95% CI: 1.3–5.5), and non-adherence to flu immunizations was observed within the agricultural industry (PR = 2.5, 95% CI: 1.1–5.7). Overall, the BRFSS can identify workplaces in need of targeted interventions to protect worker health.